Deposition of bioactive glass coatings based on a novel composition containing strontium and magnesium. Issue 13 (October 2022) - Cañas, Eugeni; Orts, María José; Sánchez, Enrique; Bellucci, Devis; Cannillo, Valeria
Abstract: In this work a novel bioactive glass composition was used to deposit coatings by means of plasma spraying. Different coatings were manufactured and optimized by varying the processing parameters and were studied by X-ray diffraction and scanning electron microscopy. Moreover, the bioactivity was assessed by in vitro tests in Simulated Body Fluid solution. The coatings displayed the typical microstructure of atmospheric plasma sprayed coatings, that is a coating made up by the stacking of melted splats, with different thicknesses, porosities and crystalline phases depending on the spraying parameters used. The work showed that all the coatings are denser and with less porosity than those observed for plasma sprayed coatings of the well-known 45S5 bioactive glass, with similar particle size deposited under the same spraying conditions. The in vitro tests demonstrated the bioactive aptitude of all the coatings, on whose surface an hydroxycarbonate apatite layer formed after 7 days of soaking.